2022
DOI: 10.1021/acsapm.2c01043
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Performance of Bioinspired PLA Fabricated via One-Step Plasma Etching with Silver and Copper

Abstract: Nanotechnology has been adopted to mimic a biological system to design artificial nanostructures with properties suitable for advanced applications. In this way, bioinspired bactericidal surfaces with surface nanostructured like insect wings display antimicrobial properties that undergo a physicomechanical mechanism that disrupts the microbial cells, inhibiting their growth and proliferation. Herein, we describe a method to design nanocone patterns on the surface of poly­(lactic acid) (PLA) via one step of arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In addition, various experimental factors such as H 2 , Ar, or O 2 partial pressure, etchant species, substrate, and buffer gas have also been observed to significantly influence the thinning behavior of 2D materials. Extensive theories have been explored and the mechanisms underlying the effects of parameters on 2D material thinning have been shown, but similar studies in another material thinning are still rare if these thinning methodologies are not only applied to 2D materials, but also applied to other materials and investigated for semiconductor devices such as polymer materials, [187][188][189][190][191][192][193] transition metal carbides, nitrides, carbonitrides (MXenes), [194][195][196][197][198][199] perovskite, [200][201][202][203][204] or thinning metal-based nanowire, nanotube, and nanorod structures. [205][206][207] The thinning advances in processing materials have the potential to open up new opportunities for the development of high-quality 2D materials that are needed for electronics and optoelectronics for suitable applications.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…In addition, various experimental factors such as H 2 , Ar, or O 2 partial pressure, etchant species, substrate, and buffer gas have also been observed to significantly influence the thinning behavior of 2D materials. Extensive theories have been explored and the mechanisms underlying the effects of parameters on 2D material thinning have been shown, but similar studies in another material thinning are still rare if these thinning methodologies are not only applied to 2D materials, but also applied to other materials and investigated for semiconductor devices such as polymer materials, [187][188][189][190][191][192][193] transition metal carbides, nitrides, carbonitrides (MXenes), [194][195][196][197][198][199] perovskite, [200][201][202][203][204] or thinning metal-based nanowire, nanotube, and nanorod structures. [205][206][207] The thinning advances in processing materials have the potential to open up new opportunities for the development of high-quality 2D materials that are needed for electronics and optoelectronics for suitable applications.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…To summarize, the surface topography of the biomaterials has a great influence on the adhesion, spreading, proliferation, and functional expression of cells. In order to fabricate different microstructures, various kinds of manufacturing techniques have been developed, such as 3D print (Zhou et al, 2016;Wu et al, 2020), plasma etching (da Silva andRosa, 2022;Ozaltin et al, 2022), lithography (Jeong et al, 2015;Sun et al, 2016), etc. However, aforesaid technologies are complex and precise control of the nanometer-sized features is still difficult to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [7] created a rough surface containing nanopores and nanospikes on stainless steel 316L by electrochemical etching, and effectively inhibited bacterial adhesion on its surface. Also, Silva et al [8] reported on a plasma etching process in the presence of silver and copper to create conical nanostructures on poly(lactic acid) (PLA) surfaces which could ultimately prevent the adhesion and growth of E. coli biofilm by ≈95% after 24 h of incubation. Other tactics to create biomimetic nanostructures include direct replication of natural structures through molding, [9] or using a variety of lithography techniques on photoresists or photoactive azobenzene materials.…”
mentioning
confidence: 99%